Developments in the supply of direct international air services from airports in Scotland. - Pagliari, Romano (Elsevier, 2005)
Scotland's location, limited population size and absence of major base carriers have served to constrain the development of direct international air services. Air service liberalisation has altered the degree to which different segments of the international passenger market are served at each airport. Overall, air service provision has been enhanced by the activities of Ryanair at Prestwick, long-haul airlines operating to Glasgow and the use of regional jets by franchise carriers at Aberdeen and Edinburgh. These initiatives, to a large extent, were as a result of promotional efforts undertaken by the airport operators. The Scottish Executive-administered Interim Route Development Fund has been less effective in this regard.
Keywords: Air services; Scotland; Scottish airports; International connectivity